Reading Popular Newtonianism : Print, the Principia, and the Dissemination of Newtonian Science - Miller, Laura, 1975- (Book collections on Project MUSE., 2017)
"Reading Popular Newtonianism focuses on the reception of Sir Isaac Newton's works in a context framed by authorship, print, editorial practices, and reading. Using sustained archival work and multiple critical approaches, Laura Miller asserts that print facilitated the mainstreaming of Newton's ideas. In addition to Newton's reading habits and his manipulation of print conventions in the Principia, she analyzes the implied readership of various "popularizations" as well actual readers whose preferences we can trace and interpret based on the New York Society Library's borrowing records. By beginning with the publication of the Principia, Miller revises the timeline in which Newton's scientific ideas entered eighteenth-century culture"--